Peningkatan Hasil Belajar Peserta Didik Materi Adaptasi Makhluk Hidup Kelas VI Melalui Penerapan Strategi Pembelajaran Berdiferensiasi - Sri Setik Nurhamami (Journal on Education, 2022)
The purpose of this study was to determine whether there was an increase in learning outcomes in Living Creatures Adaptation Materials through the application of Differentiated Learning Strategies in grade 6 students at SDN Wonokusumo VI/45 Surabaya and to find out to what extent the learning outcomes of Living Creatures Adaptation Materials increased through the application of Differentiated Learning Strategies in class students 6 SDN Wonokusumo VI/45 Surabaya. Due to the low learning outcomes of Living Creatures Adaptation Materials experienced by grade 6 students at SDN Wonokusumo VI/45 Surabaya, the authors as their class teacher are responsible for finding solutions to improve learning outcomes for Living Creatures Adaptation Materials. The perspective taken is to increase student activity in the teaching and learning process. This relates to the selection of learning models, therefore innovation in the application of learning models and methods must be carried out through the implementation of Differentiated Learning Strategies. The research was conducted with the mechanism of action of two cycles. And based on the results of data analysis, it can be concluded that there is an increase in learning outcomes in Material Adaptation of Living Things through the application of Differentiated Learning Strategies in grade 6 students at SDN Wonokusumo VI/45 Surabaya. Improving learning outcomes in Material Adaptation of Living Things through the application of Differentiated Learning Strategies in grade 6 students at SDN Wonokusumo VI/45 Surabaya an average of 22.17%.